Pengaruh Tenaga Kerja, Bahan Baku, Dan Jam Kerja Terhadap Pendapatan Usaha Pengolahan Ikan Asap Di Desa Penatarsewu Kecamatan Tanggulangin Kabupaten Sidoarjo - Dhimas Adi Subroto; Muhammad Yasin (Jurnal Kajian dan Penelitian Umum, 2023)
This study aims to prove the effect of labor, raw materials, and working hours on the income of smoked fish processing businesses in Penatarsewu Village, Tanggulangin District, Sidoarjo Regency. This research method uses quantitative methods with primary data, the data used is a questionnaire obtained from respondents of smoked fish processing entrepreneurs in Penatarsewu Village, Tanggulangin District, Sidoarjo Regency. The data analysis tool in this study is a multiple linear regression method. The results of this study prove that partially or simultaneously there is a significant influence between raw materials and working hours, while labor variables have an insignificant effect on the income of smoked fish processing businesses in Penatarsewu Village, Tanggulangin District, Sidoarjo Regency. For the effect of labor, raw materials, and labor hours simultaneously on income (Y) with an F value count of 44.235 with a significance level of 0.000. With a significance value smaller than 0.000, which is 0.000 < 0.05, it H_O rejected and H_α accepted, which means that the free variable of raw materials and working hours has a significant effect, while the free variable of labor has an insignificant effect while the labor-free variable has an insignificant effect on smoked fish processing business in Penatarsewu Village, Tanggulangin District, Sidoarjo Regency.